Immune-checkpoint inhibitors in previously treated patients with advanced or metastatic urothelial carcinoma: A systematic review and meta-analysis. (September 2018) - Di Nunno, Vincenzo; De Luca, Emmanuele; Buttigliero, Consuelo; Tucci, Marcello; Vignani, Francesca; Gatto, Lidia; Zichi, Clizia; Ardizzoni, Andrea; Di Maio, Massimo; Massari, Francesco
Highlights: Immunotherapy represents a new hope for patients with metastatic UC. Only one of two randomized trials showed a clear survival benefit with immunotherapy. The rule of PD-L1 expression as predictive response factor still remains unclear. In our meta-analysis immunotherapy resulted in a significant survival benefit. The predictive value of PD-L1 expression is far from being optimal. Abstract: Immunotherapy represents a new hope for patients with advanced urothelial carcinoma (UC). However, to date, only one of two randomized studies showed a clear survival advantage with these treatments. Aimed to investigate the role of immune-checkpoint inhibitors in patients with platinum progressed metastatic UC we performed a systematic review and meta-analysis of clinical trials to evaluate the efficacy and activity, in terms of Overall Survival (OS) and Objective Response Rate (ORR). Immune checkpoint inhibitors have showed to improve OS compared to chemotherapy in unselected patients (HR 0.80, 95% CI 0.69–0.93, p = 0.003), while the difference was not significant in patients selected for PD-L1 expression (HR 0.72, 95% CI 0.48–1.09, p = 0.12). Pooled probability of response was 0.18 (95% CI 0.16–0.20) in unselected patients and 0.27 (95% CI 0.25–0.32) in PD-L1 selected patients. Immunotherapy results in a significant survival advantage in PD-L1 unselected patients suggesting that PD-L1 expression may not be a reliable marker in previously platinum treated patients.